Confined H(1s) and H(2p) under different geometries. (2nd July 2015) - Longo, G Micca; Longo, S; Giordano, D
Abstract: In this paper the diffusion Monte Carlo method is applied to the confined hydrogen atom with different confinement geometries. This approach is validated using the much studied spherical and cylindrical confinements and then applied to cubical and squared ones, for which data are not available, as new applications of the method relevant to solid state physics. The energy eigenvalues of the ground state and one low-lying excited state are reported as a function of the characteristic confinement length.